The solution(s) to the equation x2+5x+6=−3x2−2x can be found by combining like terms and simplifying the equation.
First, we can add 3x2 and 2x to both sides, which gives us:
x^2 + 5x + 6 + 3x^2 + 2x = 0
4x^2 + 7x + 6 = 0
Next, we can factor the quadratic equation:
(4x + 3)(x + 2) = 0
Setting each factor equal to zero gives us two solutions:
4x + 3 = 0
x = -3/4
and
x + 2 = 0
x = -2
Therefore, the correct interpretation of the solution(s) to the equation x2+5x+6=−3x2−2x is x = -3/4 and x = -2.
Which statement correctly interprets the solution(s) to the equation x2+5x+6=−3x2−2x ?
1 answer